Bittersweet: The Effects of Psychological Trauma in One’s Stages of Life - Celia Asallie (Institute of Research and Community Outreach - Petra Christian University, 2018)
The project is about the development of a screenplay which explores the psychological problem of the main character. The creative work revolves around the traumatic experiences that result in the main character’s insecurity. The story shows how the main character, Jieun, is haunted by the pressure she used to have when she was a kid, causing her to feel insecure when she finally turns into an adult. The theory used for this creative work is Erik Erikson’s theory of Psychological Stages of Development which tells about how something that happened in the past could affect things that are happening in the present. The theory helps the writer achieve the result of the creative work, making the creative work have distinct characteristic. Because of her insecurity, Jieun fails in fulfilling her need to build a relationship. Finally, she regains her feeling of security as she goes back to and connect with her family.